FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMAKAIAN KONTRASEPSI KONDOM PADA PASANGAN USIA SUBUR DI WILAYAH KERJA PUSKESMAS CAMPALAGIAN - Muliyana; Reskiawati Azis (Stikes Graha Edukasi Makassar, 2021)
The research objective: To determine the factors associated with the use of contraceptive condoms in fertile aged couples in the Campalagian Community Health Center. Methods: This study is an analytical survey research with a